Diagnosing autistic spectrum disorder in the age of austerity. Issue 1 (20th June 2012) - Karim, K.; Cook, L.; O'Reilly, M.
Abstract Background Diagnosing autistic spectrum disorder is a challenge, typically involving myriad professionals. In the current climate we explore how diagnosis is managed in the real world by professionals. Methods Using semi‐structured interviews we thematically analyse data from psychiatrists, paediatricians and educational psychologists. Results While there is some consistency across and within these groups there are also a number of variances, and several important issues are highlighted. These include the problem of time and resources, the issue of location for diagnosis, the value of diagnostic tools and schedules, the need for supporting information, the difficulty of multi‐agency working, the relevance of a physical examination and the eventual diagnostic label. Conclusions In the current economic climate and considering changes in guidelines there is a need to evaluate current service provision and enhance services. However, attention needs to be paid to the practical and realistic application of the suggested guidance.